2005
DOI: 10.1590/s0100-879x2005000700011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine on the electrophysiological, cognitive and motor responses of the central nervous system

Abstract: Caffeine is the most consumed psychoactive substance in the world. The effects of caffeine have been studied using cognitive and motor measures, quantitative electroencephalography (qEEG) and event-related potentials. However, these methods are not usually employed in combination, a fact that impairs the interpretation of the results. The objective of the present study was to analyze changes in electrophysiological, cognitive and motor variables with the ingestion of caffeine, and to relate central to peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 39 publications
5
29
1
2
Order By: Relevance
“…It has been reported that caffeine increases alertness and speeds reaction time, dominant factors in relation to alpha power (Fredholm et al 1999;Smith 2002). In addition, previous studies reported a drop in absolute alpha power during rest with eyes open when caffeine was ingested at high doses (Deslandes et al 2005;Siepmann and Kirch 2002). In our study, caffeine assessed in the saliva did not show detectable values (above the device's quantification limit ϭ 2 g/ml), suggesting that caffeinated drinks did not bias the observed results.…”
Section: Discussionsupporting
confidence: 45%
“…It has been reported that caffeine increases alertness and speeds reaction time, dominant factors in relation to alpha power (Fredholm et al 1999;Smith 2002). In addition, previous studies reported a drop in absolute alpha power during rest with eyes open when caffeine was ingested at high doses (Deslandes et al 2005;Siepmann and Kirch 2002). In our study, caffeine assessed in the saliva did not show detectable values (above the device's quantification limit ϭ 2 g/ml), suggesting that caffeinated drinks did not bias the observed results.…”
Section: Discussionsupporting
confidence: 45%
“…Studies that have combined caffeine ingestion and P300 measures have shown conflicting results. In the current literature there are studies showing no alteration [32] , alterations in just the amplitude [17] , or latency [4] , or both [33] , related or not to an improvement in performance. The variability among subjects may account for such results, since P300 is greatly affected by biological determinants, such as food ingestion, temperature, hours of sleep and the individual's mood [15] .…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have identified caffeine as a stimulant using motor, behavioral and electrophysiological measures [4][5][6][7][8] . However, other studies failed to demonstrate caffeine effects on cognitive functions, such as attention and memory [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Estudos recentes têm sugerido que a substância investigada poderia proporcionar um impacto relevante sobre o estado de humor (DUNCAN; OXFORD, 2011;BELL, 2001;RUXTON, 2008;DESLANDES at al., 2005). Entretanto, nenhuma alteração significante foi constatada no presente estudo para os parâmetros de confusão, raiva, depressão, fadiga, tensão e vigor após ingestão de cafeína.…”
Section: Discussionunclassified
“…Alterações da sensação de humor estão atreladas à prática de exercício de alta intensidade e longa duração, em geral, associadas a ambientes quentes e secos (RUXTON, 2008). Da mesma forma, Deslandes et al (2005) não detectaram alterações causadas pela ingestão de cafeína no estado de humor e no desempenho cognitivo, bem como nas áreas cerebrais relacionadas. Ressalta-se que os estudos são inconcluvivos quanto o real efeito cognitivo e de humor associado ao consumo da cafeína (CROWE, 2006;RUXTON, 2008).…”
Section: Discussionunclassified